The Saami drums and the religious encounter in the 17th and 18th centuries - Rydving, Håkan (Scripta Instituti Donneriani Aboensis, 1991)
From the end of the 17th to the middle of the 18th century much of the confrontation between indigenous Saami religion and Christianity was focused on the drums. The Saamis of both Denmark—Norway and Sweden—Finland had been christianized for decade. The main problem for the Church authorities turned out to be that of making the Saamis abandon their indigenous religious customs. From the end of the 17th century, an intense period of propaganda and coercion began to make the Saamis abandon these non Christian elements in their religion. For the Saamis, the drums represented their threatened culture, the resistance against the Christian claim to exclusiveness, and a striving to preserve traditional values. The drums had a twofold role to play in the religious encounter. They were both foci of the confrontation and sources documenting and structuring it. The fight between old and new beliefs is to some extent possible to follow in the records from the district and county courts. These records give us access to Saami arguments and views of the importance of the drums in Saami society. The function of the drums as instruments for a Saami description of the encounter is, however, difficult to make out. The drum figures are difficult to interpret and there are a number of alternative ways of understanding their meaning.
Keywords: Sami (European people); Shamanism; Shamans; Ritual; Drum; Scandinavia; Christianity; Church history; Symbolism; Musical instruments